Identifikasi dan Karakterisasi Buah-buahan di Kabupaten Karangasem - SURYAWAN, I MADE ANANTA; WAJANA, GEDE; ASTAWA, I NYOMAN GEDE (Agrotrop : Journal on Agriculture Science, 2016)
Identification and Characterization of Fruits in Karangasem Regency. The fruits in aregion has the potential to be developed. The fruits in Karangasem Regency, Bali, need to bedeveloped, due to economic value, role in the socio-cultural (religious rituals), SPA facilities,and participating in trade within the country and export. In developing the genetic resourcesof the fruit is a need to identify, characterize, and preparation of maps geographic distributionof fruit. The study aims to identify, characterize, and preparation of maps geographicdistribution of fruit. The study consisted of five phases of activities, namely: (1) secondarydata collection, (2) identification of the type and cultivar, (3) identification of agronomiccharacterization, (4) determine the seeded fruit, (5) make a map of the geographicaldistribution of fruit in Karangasem regency. The results showed that identified 37 species and59 cultivar of fruit contained in Karangasem Regency, composed of 59 pieces profileKarangasem Regency, and made the maps geographic distribution of salak fruit inKarangasem Regency.
Keywords: characterization; fruits; Karangasem Regency; identification